Functional blockade of cancer-associated fibroblasts with ultrafine gold nanomaterials causes an unprecedented bystander antitumoral effect. Issue 38 (24th September 2020) - Xia, Chengwan; Pan, Jiongru; Wang, Jianquan; Pu, Yumei; Zhang, Qian; Hu, Shiqi; Hu, Qingang; Wang, Yuxin
Abstract : Gold nanoparticles (GNPs) exhibited unprecedented size dependent anti-CAF potential, wherein the smallest GNPs outperformed their larger counterparts. Abstract : Cancer-associated fibroblasts (CAFs) play a critical role in the onset and progression of malignancies, such as oral squamous cell carcinoma (OSCC), making CAFs a promising druggable target. In this study, gold nanoparticles (GNPs) exhibited unprecedented size dependent anti-CAF potential, wherein the smallest GNPs outperformed their larger counterparts. Specifically, a subset of proteins and cytokines that is responsible for the invasive outgrowth of OSCC cells was found to decrease post exposure of OSCC patient-derived CAFs to GNPs. Moreover, the administration of GNPs (3 nm in diameter) could effectively abrogate the growth of OSCC tumors in vivo, offering a novel means to manage OSCC in the clinic. Besides targeting cancer cells, our results collectively verify the feasibility of blocking dominant cells in the microenvironment to eradicate tumors, shedding light on the future design of nanomedicines.